Fidaxomicin for the treatment of Clostridioides difficile in children - Skinner, Andrew M (Future Microbiol, 2020)
Fidaxomicin is an oral narrow-spectrum novel 18-membered macrocyclic antibiotic that was initially approved in 2011 by the US FDA for the treatment of Clostridioides difficile infections (CDI) in adults. In February 2020, the FDA approved fidaxomicin for the treatment of CDI in children age >6 months. In adults, fidaxomicin is as efficacious as vancomycin in treating CDI and reduces the risk of recurrent CDI. An investigator-blinded, randomized, multicenter, multinational clinical trial comparing the efficacy and safety of fidaxomicin with vancomycin in children was recently published confirming similar findings as previously reported in adults. Fidaxomicin is the first FDA-approved treatment for CDI in children and offers a promising option for reducing recurrent CDI in this population.